Empreendedores da cena noturna: uma análise do trabalho de promoters de eventos artístico-musicais na cidade de São Paulo - Pina, Marcos Roberto Mariano (2014)
With the advent of the flexibilization of labor and production relations, a large number of new features and values gained prominence in the analysis of the work category, aiming, among other things, at the increasing individualization of the responsibilities in the work processes, the new lean organizations and the work based on short duration projects, as opposed to the preceding moment of the wage labor model called Fordist-Keynesianist. The analysis of the occupational career of party organizers in the night entertainment in the city of São Paulo has provided a very representative empirical cut on the flexibility expected of contemporary workers. We observed the forms of entry and maintenance on this informal market, mainly associated with the possession of a differentiated social capital, mobilized in accord to the cultural prescriptions of the consumer groups. We also analyzed the subjective and objective efforts demanded in their daily activities, that mobilizes great physical and mental efforts and dominate large periods of their personal schedules, and yet are positively reinterpreted as values of entrepreneurship and creative freedom. We observed how their identity as workers were constructed based on this differentiated service business, selling a product characterized by its symbolic value. We interviewed 8 Promoters from different musical styles, using semi-structured and free interviews, conducted in person or through virtual platforms of interaction, which are the spaces par excellence of the dissemination and promotion of their own parties.